CLINICAL STUDY OF DRUG REACTION WITH EOSINOPHILIA AND SYSTEMIC SYMPTOMS (DRESS) – WITH SPECIAL FOCUS ON THE INCITING DRUG AND THE INDICATION FOR STARTING THE DRUG - ZACHARIA, MERIYA; P, SEENA; SHAJ, KIRAN; KESIEZIE, NEIKHRIETSONUO (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study was undertaken to identify the most common drug causing drug reaction with eosinophilia and systemic symptoms (DRESS) inpatients admitted in our center and possible factors associated with it. Methods: This was a cross-sectional observational study of patients with DRESS admitted from January 2018 to December 2020. Data were entered in MS Excel and analyzed using SPSS software. Results: Eighty-four consecutive patients who were diagnosed as DRESS were included in the study. The most common inciting drug was phenytoin and the most common indication for starting phenytoin was traumatic brain injury (TBI) to prevent seizures. DRESS to phenytoin after neurotrauma (NT) was more in patients who sustained combined extradural (EDH) and subdural hematoma (SDH), and those were managed conservatively for NT. None of the patients recognized fever as an initial feature of DRESS and did not stop the drug. More than one-third of patients with erythema multiforme (EM) like rash developed drug induced liver injury(DILI). The majority of patients who had sub-arachnoid hemorrhage (SAH) developed DILI. Conclusion: Phenytoin though time-tested and cost-effective for prevention of seizures after TBI, it very commonly leads to DRESS which adds to the morbidity and rarely mortality of patient. In this present era of increasing road traffic accidents, using newer non-aromatic anticonvulsants may be more beneficial than phenytoin. The patients should be made aware of the likely time DRESS can occur, the earliest symptom of DRESS, and the need to stop the drug at the earliest.